2021
DOI: 10.3389/fgene.2021.656061
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Adaptive Evolution of Sand Rice (Agriophyllum squarrosum) and Its Implications for Desert Ecosystem Restoration

Abstract: Natural selection is a significant driver of population divergence and speciation of plants. Due to local adaptation to geographic regions with ecological gradients, plant populations harbored a wide range of adaptive genetic variation to enable them to survive the heterogeneous habitats. This is all the more necessary for desert plants, as they must tolerant more striking gradients of abiotic stresses. However, the genomic mechanism by which desert plants adapt to ecological heterogeneity remains unclear, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Previous studies showed that there was no significant divergence among the altitudinal wild populations in neutral molecular genetic markers (nrITS and chloroplast DNA; Qian et al, 2016 , 2021 ). However, non-target metabolomics analysis supported that the accumulations of a couple of flavonoids, such as hesperetin, quercetin, and apigenin, were significantly enriched in the ecotype with high altitude (unpublished data).…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies showed that there was no significant divergence among the altitudinal wild populations in neutral molecular genetic markers (nrITS and chloroplast DNA; Qian et al, 2016 , 2021 ). However, non-target metabolomics analysis supported that the accumulations of a couple of flavonoids, such as hesperetin, quercetin, and apigenin, were significantly enriched in the ecotype with high altitude (unpublished data).…”
Section: Introductionmentioning
confidence: 94%
“…Sandrice [ Agriophyllum squarrosum (L.)] is an edible and medicinal resource psammophyte of Chenopodiaceae, which is widely distributed in the vast arid and semi-arid sandy lands in Central Asia, the Caucasus, Mongolia, Siberia, and Northern China ( Qian et al, 2016 ). Sandrice is a pioneer species on mobile sands, being able to adapt to the cruel environment in deserts like extreme temperature, dehydration, and sand burial, and was proved to have a wide range of genetic and phenotypic variation among different populations, which was derived from local adaptation to their original marginal habitats ( Yin et al, 2016 ; Zhao et al, 2017 , 2022 ; Qian et al, 2021 ). Although this underutilized feed crop has not been domesticated, the seeds of sandrice have a long consumption history and are rich in essential amino acids, crude fiber, polyunsaturated fatty acids, etc., and tender stems and leaves of sandrice are wild feedings for livestock in the sandy areas, making it an ideal functional food and natural feed crop ( Li et al, 1992 ; Chen et al, 2014 ; Wang Q. et al, 2019 ; Han et al, 2021 ; Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…7D–F ), indicating that the plasticity of seed size is heritable and potentially adaptive. Population genetic analyses have consistently indicated that genetic divergence mainly occurs between populations from the eastern sand fields and those from the central and western deserts in Northern China ( Qian et al ., 2016 , 2021 ). Our previous haplotype analysis of a seed size candidate gene, DA1-Related , also showed a similar divergence pattern among natural populations of sand rice ( Zhao et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%